"Kia ora. This is my earthquake story". Multiple applications of a sociolinguistic corpus. (2016) - Clark, Lynn; MacGougan, Helen; Hay, Jennifer; Walsh, Liam
Abstract: This paper demonstrates how spoken data, collected using sociolinguistic methods, can have multiple applications outside of its original intended use within sociolinguistics. It can be a resource for tackling real-world problems, it can be a platform for community engagement and it can function as a source of data for academic research (both linguistic and non-linguistic research). The spoken data we describe is a new corpus of monologues called the UC QuakeBox corpus. First, we introduce and demonstrate the QuakeBox corpus, and outline some of the rewards and challenges associated with collecting stories in a manner that was purposefully and saliently in the public eye. Next, we focus on applications of the QuakeBox corpus by exploring case studies which are utilising data from the corpus for non-linguistic work. We situate this work within the wider field of applied sociolinguistics. Highlights: This paper demonstrates how a corpus of spoken data can have multiple applications outside of linguistics. The QuakeBox corpus has been used in: The construction of a set of teaching resources for the high school curriculum. A study of the experiences and emotional responses of teachers. A project which seeks to examine water and waste activities in the wake of damaged sanitation infrastructure.